Garcinia sibeswarii (Clusiaceae), a new species from Assam, India - Shameer, Peerumuhammed Subaida; Sarma, Jatindra; Mohanan, Narayanan Nair; Begum, Ajima (Phytotaxa, 2021)
Garcinia sibeswarii, a new species of Garcinia from the Dulang Reserve Forest, Assam, North East India is described and illustrated. The new species is allied to Garcinia celebica, but differs in having 4-celled ovary; entire, peltate, reddish stigma and seeds with fibrous aril.